Wpływ pracy zawodowej na występowanie zespołów bólowych kręgosłupa na przykładzie pielęgniarek województwa kujawsko - pomorskiego = The impact of work on the occurrence of back pains on the example of nurses in the Kujawsko-Pomorskie voievodeship - Karolina Juraszek; Magdalena Hagner-Derengowska; Magdalena Hoffmann; Zdzisława Kalisz; Walery Zukow (Kazimierz Wielki University, 2016)
Juraszek Karolina, Hagner-Derengowska Magdalena, Hoffmann Magdalena, Kalisz Zdzisława, Zukow Walery. Wpływ pracy zawodowej na występowanie zespołów bólowych kręgosłupa na przykładzie pielęgniarek województwa kujawsko - pomorskiego = The impact of work on the occurrence of back pains on the example of nurses in the Kujawsko-Pomorskie voievodeship. Journal of Education, Health and Sport. 2016;6(8):504-521. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60944 http://ojs.ukw.edu.pl/index.php/johs/article/view/3788       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 25.08.2016.     Wpływ pracy zawodowej na występowanie zespołów bólowych kręgosłupa na przykładzie pielęgniarek województwa kujawsko - pomorskiego The impact of work on the occurrence of back pains on the example of nurses in the Kujawsko-Pomorskie voievodeship   Karolina Juraszek2, 4, Magdalena Hagner-Derengowska1, 2, Magdalena Hoffmann3, Zdzisława Kalisz2, Walery Zukow5   1. Katedra Neuropsychologii Klinicznej Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Bydgoska Szkoła Wyższa w Bydgoszczy 3. Uniwersyteckie Centrum Kliniczne w Gdańsku, Klinika Nadciśnienia Tętniczego i Diabetologii 4. Centrum Onkologii im. prof. F. Łukaszczyka w Bydgoszczy, Zakład Rehabilitacji 5. Uniwersytet Kazimierza Wielkiego w Bydgoszczy     Słowa kluczowe: praca, zespoły bólowe kręgosłupa, pielęgniarki Key words: work, back pain, nurses Streszczenie Zdrowie człowieka w dużym stopniu determinują czynniki środowiskowe, wśród których ogromny wpływ na prawidłowe funkcjonowanie wywiera charakter wykonywanej pracy i obciążenia jakie za sobą niesie. Obecnie jedną z głównych schorzeń pracowników podmiotów leczniczych są przeciążenia układu mięśniowo-szkieletowego, wśród których zespoły bólowe kręgosłupa stanowią drugą pod względem częstości przyczynę absencji w pracy. Grupę badawczą stanowiło 205 zawodowo czynnych pielęgniarek z różnych grup wiekowych. W grupie badanych pielęgniarek badania wykazały niepokojąco mały odstetek osób posiadająych wiedzę na temat norm dźwiagania cieżarów u kobiet. Również nie wszystkie pielęgniarki znają i przyjmują prawidłową pozycję podczas dźwiagania pacjentów. Mimo to są zdania, że posiadają potrzebną wiedzę odnośnie ergonomii i profilaktyki w pracy. Analiza występowania zespołów bólowych kręgosłupa w grupie pielęgniarek potwierdziła niekorzystny wpływ pracy na organizm, jak również nakreślila podłoże problemu związane nie tylko ze specyfiką wykonywanych czynności w pracy, ale również z niedostatecznym przeszkoleniem odnośnie bezpieczeństwa i profilaktyki przeciążenia narządu ruchu na stanowisku pracy.   Abstract   Human health is largely determined by the environmental factors, among which the nature of the work and load that it carries has a huge impact on the proper functioning of the body. Currently one of the major diseases of health service employees is overload of the musculoskeletal system, including back pain as a second most common cause of absenteeism. The study group consisted of 205 professionally active nurses from different age groups. In the surveyed group of nurses studies showed an alarmingly small percentage of people aware of lifting standards for women. Also, not all nurses know and assume the correct position when lifting patients. The occurrence of back pains in the group of nurses confirmed the negative impact of work on the body. It outlined the base of the problem related not only to the specific nature of activities performed at work, but also to insufficient training for health and safety of musculoskeletal overload in the workplace.